Endovascular treatment of a craniocervical junction dural arteriovenous fistula associated with lateral medullary syndrome: A case report - Masaaki Kubota, MD, PhD; Yosuke Tajima, MD, PhD; Yoshinori Higuchi, MD, PhD (Radiology Case Reports)
Intracranial dural arteriovenous fistulas (DAVFs) with drainage into the perimedullary veins have been reported to cause brainstem and spinal hemorrhages, subarachnoid hemorrhages, and progressive myelopathy. However, there have been no reports of craniocervical junction arteriovenous fistulas (CCJ-AVFs) complicated by lateral medullary syndrome (LMS) and subsequently treated. We present a case successfully treated with transvenous and transarterial embolization. A 67-year-old man presented with headache and dizziness was diagnosed with left LMS based on diffusion-weighted MRI. MRA ruled out vertebral artery dissection and posterior inferior cerebellar artery occlusion but suggested an arteriovenous shunt at the CCJ, which digital subtraction angiography confirmed as a DAVF fed by the radiculomeningeal artery with drainage into the anterior lateral spinal vein and deep brainstem veins. To minimize embolic complications, transvenous embolization with coils was performed first, followed by transarterial embolization with N-butyl cyanoacrylate. Postoperative MRI showed resolution of venous engorgement, and the patient was discharged without additional neurological deficits. This case highlights the potential role of AVF-induced venous engorgement in brainstem infarction and underscores the importance of early diagnosis and individualized treatment. A combined transvenous and transarterial approach can effectively control ascending venous outflow while minimizing procedural risks.